Bilişsel ve üst-biliş stratejilerinin kullanımı ile yabancı dil testlerindeki performans arasındaki ilişki - Değirmenci, İsmail Lütfü (My University, 2005)
The relationship between the cognitive and metacognitive strategy use and the performance on a second language test by İsmail Lütfü Değirmenci The present study aims to investigate the effects of cognitive and metacognitive strategy use of language learners on their second language test performance. The following research questions are particularly addressed: 1.What is the relationship between learners' reported use of cognitive and metacognitive strategies and their performance on a second language test? 2.Is there a statistically significant difference between high and low ability learners in terms of their cognitive and metacognitive strategy use? 3.Do the test-takers' reported use of cognitive and metacognitive strategies differ according to : a)gender? b)whether they are a senior class student or a graduate? c)the type of the school they attend / graduated from? d)whether they had a preparation class education? e)how long they have attended a university entrance exam preparatory course? f)the extent to which they believe they perform what they actually can on the English tests? Data were collected from 303 students attending a university exam preparatory course forming 17 groups at various levels. In order to determine the students' performance on a second language test, the participants were given an English Proficiency Test. They were also given a Language Learning Strategy Questionnaire and a Background Questionnaire to obtain data relevant to the research questions. Furthermore, through semi-structured interviews qualitative data were obtained from 8 students. Findings revealed that there was a significant correlation between the English Proficiency Test performance and the cognitive and metacognitive strategy use. Another finding of the study was that both cognitive and metacognitive strategy scores of the high ability students were significantly higher than those of the low ability students. With respect to gender, for both cognitive and metacognitive strategy use, females presented more strategy use than males. In terms of cognitive and metacognitive strategy use, results revealed no significant difference both with respect to whether the students had attended the university entrance exam preparatory course for one year or two years or more and whether they were a senior class student or a graduate. Moreover, whether the students had a preparation class education or not did not have an effect on strategy use, either. As regards lycee types, the results indicated a significant difference. Generally, Super Lycee students and Anatolian High School students displayed more strategy use than public school and private school students. Another finding of the study was that the cognitive strategy scores of the students who thought they performed less than what they actually could on the English tests was significantly higher than those of the students who thought they performed what they actually could. In terms of metacognitive strategy use no difference was detected. The discussion of the findings was presented and in the light of these findings, limitations of the study were mentioned. KISA

Bilişsel ve üst-biliş stratejilerinin kullanımı ile yabancı dil testlerindeki performans arasındaki ilişki İsmail Lütfü Değirmenci Bu çalışmanın amacı öğrencilerin yabancı dil testlerindeki bilişsel ve üst-biliş strateji kullanımlarının yabancı dil testlerindeki performansları üzerindeki etkisini araştırmaktır. Çalışma özellikle aşağıdaki soruları yanıtlamayı amaçlamaktadır: 1.Öğrencilerin belirttikleri bilişsel ve üstbiliş strateji kullanımları ile yapancı dil testindeki performansları arasındaki ilişki nedir? 2.Yüksek ve düşük beceri seviyesindeki öğrenciler arasında bilişsel ve üstbiliş strateji kullanımları açısından istatiksel bir fark var mıdır? 3.Öğrencilerin belirttikleri bilişsel ve üstbiliş strateji kullanımlarında aşağıdaki değişkenlere göre farklılık var mıdır? a)cinsiyet b)Lise 3 öğrencisi veya mezun olma durumu c)devam ettikleri veya mezun oldukları okul türü d)hazırlık sınıfı eğitimi alıp almadıkları e)üniversite hazırlık kursuna devam ettikleri süre f)sahip oldukları İngilizce bilgisini testlere ne oranda yansıtabildikleri hakkındaki düşünceleri Çalışma için gerekli olan veriler bir üniversite hazırlık kursuna devam eden ve 17 gruba ayrılmış 303 öğrencinin örneklem teşkil etmesi ile elde edilmiştir. Öğrencilerin yabancı dil testindeki performansları bir İngilizce Yeterlilik Testi uygulanarak ölçülmüştür. Amaçlanan araştırma soruları ile ilgili veri toplamak amacı ile, öğrencilere ayrıca Yabancı Dil Öğrenimi Strateji Kullanım Anketi ile Kişisel Bilgi Anketi uygulanmıştır. Ayrıca görüşme yöntemi ile 8 öğrenciden nitel veri toplanmıştır. Çalışmadan elde edilen bulgular bilişsel ve üstbiliş strateji kullanımı ile yabancı dil testindeki performans arasında anlamlı bir ilişki olduğunu göstermiştir. Yüksek beceri seviyesindeki öğrencilerin bilişsel ve üstbiliş strateji kullanımlarının düşük becerideki öğrencilerden anlamlı şekilde yüksek olduğu görülmüştür. Çalışmadan elde edilen bulgular kız öğrencilerin hem bilişsel hem de üstbiliş stratejileri açısından erkek öğrencilerden daha fazla strateji kullandıklarını ortaya çıkarmıştır. Öğrencilerin Lise 3 öğrencisi veya mezun olmalarının, üniversite hazırlık kursuna devam ettikleri sürenin ve hazırlık sınıfı eğitimi almış olmalarının bilişsel ve üstbiliş strateji kullanımı üzerinde anlamlı bir etkisine rastlanmamıştır. Lise türü açısından Süper Lise ve Anadolu Lisesi öğrencilerinin devlet ve özel okul öğrencilerine göre daha fazla strateji kullanımı bildirdikleri tespit edilmiştir. Sahip oldukları İngilizce bilgisini testlere yansıtamadığını düşünen öğrencilerin bilişsel strateji kullanım puanlarının sahip oldukları İngilizce bilgisini testlere yansıtabildiğini düşünen öğrencilerden daha yüksek olduğu görülmüştür. Üstbiliş stratejileri açısından iki grup arasında bir farka saptanmamıştır. Çalışmanın sonunda elde edilen bulguların değerlendirilmesi yapılmış ve bu bulgular ışığında araştırmadaki sınırlayıcı etmenler belirtilmiştir.
Keywords: Dil; İngiliz Dili_Öğrenim ve Öğretim; İngilizce; Uygulamalı dilbilim